A case of giant cell tumor of the breast, clinically suspected as malignant breast tumor - Mitsuo Terada; Naomi Gondo; Masataka Sawaki; Masaya Hattori; Akiyo Yoshimura; Haruru Kotani; Yayoi Adachi; Madoka Iwase; Ayumi Kataoka; Kayoko Sugino; Makiko Mori; Nanae Horisawa; et al. (Surgical Case Reports)
Abstract Background Giant cell tumor (GCT) of the breast is scarce. We report a case of GCT of the breast which was suspected as a malignant breast tumor. Case presentation A 74-year-old woman noticed a tender lump in her right breast. We suspected a malignant tumor spreading widely with axillary lymph node metastasis on clinical examination and imaging. Histological evaluation of the biopsy tissue revealed a tumor composed the proliferation of oval to spindle-shaped cells and multinucleated giant cells without malignant epithelial cells. The tumor cells stained positively for CD68 and negatively for estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2. The pathological findings suggested GCT, and fine needle aspiration biopsy for the axillary lymph node was negative. However, there was a gap between the clinical presentation, such as a tender mass suggesting rapid growth and multiple lymphadenopathies, and the pathological presentation of biopsy, which made us hesitate to conclude GCT as the final preoperative diagnosis. We could not rule out the possibility of malignant tumors with OGCs before surgery. We performed mastectomy and sentinel lymph node biopsy according to a surgical procedure for node-negative breast cancer with a wide ductal spread. The resected tissue histologically showed the same findings to the biopsy tissue. The definitive diagnosis of GCT of the breast was given, because the tumor lacked epithelial components, marked cellular atypia, and pleomorphism. Conclusions GCT of the breast occasionally pretends as breast malignant tumors. Complete tumor resection should be performed for local control and the definitive diagnosis.